Upside-down position for the out of hospital management of children with supraventricular tachycardia. (1st February 2018) - Bronzetti, Gabriele; Brighenti, Maurizio; Mariucci, Elisabetta; Fabi, Marianna; Lanari, Marcello; Bonvicini, Marco; Gargiulo, Gaetano; Pession, Andrea
Abstract: Background: The upside-down position is a little known modified Valsalva manoeuvre (VM). The aim of this study was to investigate the safety and the efficacy of the upside-down position for the treatment of paroxysmal SVT in children. Methods: Twenty-four paediatric patients followed for SVT were enrolled. The patients were assigned (1:1) to a standard VM or to an upside-down position at the first episode of SVT at home. If no cardioversion occurred, a second attempt was undertaken with the other VM. At the patient's first relapse, the intervention protocol was applied in the opposite order at home. Results: The upside-down position compared to standard VM reached 67% vs 33% rate of cardioversion at a first attempt, followed by 50% vs 0% rate of cardioversion in patients who had failed the first attempt. After having reversed the order of intervention in case of SVT recurrence, we recorded 67% vs 25% and 71% vs 42% success rates in favour of the upside-down position. There were no adverse events. Conclusion: The upside-down position was safe and tended to be more effective than standard VM for out of hospital SVT treatment. Doctors and parents should be more aware of this effective but overlooked manoeuvre.